Psychometric Properties of the Indonesian Version of Youth Quality of Life-Weight Instrument (YQOL-W) - Grace Helena Firmansyah Putri; Fredrick Dermawan Purba (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2022)
Quality of life refers to a broad concept that describes life satisfaction in terms of culture, value, and life experiences which are used to explain someone’s life aspect in general or specifically in relation to a particular condition, such as being overweight or obese. Obesity causes many health problems and affects the overall quality of life. As the obesity rate continues to be a growing public health problem in Indonesian adolescents, examining the perceptions regarding their weight is fundamental for planning a proper intervention. However, there has been little reported of available weight-specific instruments that measure the QoL in Indonesia. Youth Quality of Life-Weight (YQOL-W) is a multicultural measurement of QoL-weight that was specifically recommended by previous researchers to measure the QoL of adolescents with obesity and overweight conditions. This study was conducted to evaluate the psychometric properties of the adapted YQOL-W instrument for Indonesian adolescents. Twenty-one items were administered to 880 adolescents between 11 and 18 years of age, of whom 54.55% were female and 71.14% were junior high school students. Data were collected with a convenience sampling technique. Confirmatory factor analysis showed that a three-factor model had an acceptable model fit, including a Self factor (4 items), Social factor (12 items), and Environment factor (5 items) with p < .05. The YQOL-W instrument had good internal consistency reliability with Cronbach’s alpha ranging from .87 to .95 and acceptable test-retest reliability with the intraclass correlation coefficients (ICC) all greater than .70. The one-factor and three-factor scores were negatively correlated with BMI and positively correlated with PedsQL (all at p < .01 level). In conclusion, the Indonesian version of the YQOL-W shows good reliability and validity for assessing the weight-specific QoL of adolescents in Indonesia.